2018
DOI: 10.1186/s12906-018-2099-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of Garcinia cambogia/Glucomannan on weight loss in people with obesity, PLIN4, FTO and Trp64Arg polymorphisms

Abstract: BackgroundOverweight and obesity are considered major health problems that contribute to increase mortality and quality of life. Both conditions have a high prevalence across the world reaching epidemic numbers. Our aim was to evaluate the effects of the administration of Garcinia cambogia (GC) and Glucomannan (GNN) on long-term weight loss in people with overweight or obesity.MethodsProspective, not-randomized controlled intervention trial was conducted. We treated 214 subjects with overweight or obesity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
2
22
0
5
Order By: Relevance
“…Obesity has been associated with a number of conditions like fatty liver disease, osteoarthritis, digestive problems, cardiovascular disease, type II Diabetes Mellitus, and even some forms of cancer [11]. Along with its consequent comorbidities, obesity represents a socio-economic burden which has been shown to reduce life expectancy significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been associated with a number of conditions like fatty liver disease, osteoarthritis, digestive problems, cardiovascular disease, type II Diabetes Mellitus, and even some forms of cancer [11]. Along with its consequent comorbidities, obesity represents a socio-economic burden which has been shown to reduce life expectancy significantly.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies of the effects of lifestyle interventions among obese individuals have revealed that rs4994 C allele carriers show less weight reduction in comparison to other obese subjects [17,46,47], although several studies have shown conflicting results [48,49]. Our results suggest that in combination with the strict weight control (e.g., aimed at achieving a BMI of <23 kg/m 2 in Japanese individuals), ADRB3 rs4994 polymorphism genotyping may provide a useful information to reduce the risk of developing NAFLD in individuals with the C/C genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, a prospective, non-randomized controlled trial suggested a possible beneficial role of glucomannan on weight loss in overweight subjects treated with a combination of Garcinia Cambogia and glucomannan at a dosage of 500 mg, twice a day, for six months. However, the administration in association with Garcinia Cambogia made the individual effect of GMM indistinguishable [98]. Finally, Onakpoya et al, in a systematic review and metanalysis of nine trials, indicated that glucomannan intake does not generate a significant decrease in body weight or BMI when compared to placebo [99].…”
Section: Glucomannanmentioning
confidence: 99%